Antimicrobial Potential of Lycosin-I, a Cationic and Amphiphilic Peptide from the Venom of the Spider Lycosa singorensis - Tan, H.; Ding, X.; Meng, S.; Liu, C.; Wang, H.; Xia, L.; Liu, Z.; Liang, S. (Current Molecular Medicine, 2013)
Antimicrobial peptides (AMPs) are significant components of the innate immune system and play indispensable roles in the resistance to bacterial infection. Here, we investigated the antimicrobial activity of lycosin-I, a 24-residue cationic anticancer peptide derived from Lycosa singorensis with high structural similarity to several cationic and amphiphilic antimicrobial peptides. The antimicrobial activity of lycosin-I against 27 strains of microbes including bacteria and fungi was examined and compared with that of the Xenopus-derived AMP magainin 2 using a microdilution assay. Lycosin-I inhibited the growth of most microorganisms at low micromolar concentrations, and was a more potent inhibitor than magainin 2. Lycosin-I showed rapid, selective and broad-spectrum bactericidal activity and a synergistic effect with traditional antibiotics. In vivo, it showed potent bactericidal activity in a mouse thigh infection model. High Mg2+ concentrations reduced the antibacterial effect of lycosin-I, implying that the peptide might directly interact with the bacterial cell membrane. Uptake of the fluorogenic dye SYTOX and changes in the surface of lycosin-Itreated bacterial cells observed by scanning electron microscopy confirmed that lycosin-I permeabilized the cell membrane, resulting in the rapid bactericidal effect. Taken together, our findings indicate that lycosin-I is a promising peptide with the potential for the development of novel antibacterial agents.
Keywords: antimicrobial peptide